2012
DOI: 10.1007/s10535-012-0104-4
|View full text |Cite
|
Sign up to set email alerts
|

Sodium nitroprusside modulates gene expression involved in glutathione synthesis in Zea mays leaves

Abstract: To investigate a possible involvement of nitric oxide in gene regulation of glutathione and flavonoid synthesis pathways, maize seedlings were treated with sodium nitroprusside (SNP), a NO donor, and apocynin (APO), an inducer of NO production. After 12-h treatment, the transcripts of γ-glutamylcysteine synthetase (γ-ecs) , glutathione synthetase (gsh-s), chalcone synthase (chs), phenylalanine ammonia lyase (pal.1), myb-related protein P (P1) and actin 1 (act) genes were quantified in maize leaves by real tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Both, loss of GSNOR function and fumigation with NO enhanced GSH level ( Figures 3A,C ) assuming that NO/SNO is able to stimulate the GSH biosynthesis pathway. These measurements coincide with previous reports demonstrating a higher amount of GSH in roots of Medicago truncatula (Innocenti et al, 2007) and maize leaves (Mello et al, 2012) after GSNO and SNP treatment, respectively. In both cases, an enhanced expression of the γ-glutamylcysteine synthetase and GSH synthetase gene was detectable suggesting a NO-dependent transcriptional regulation of GSH production.…”
Section: Discussionsupporting
confidence: 92%
“…Both, loss of GSNOR function and fumigation with NO enhanced GSH level ( Figures 3A,C ) assuming that NO/SNO is able to stimulate the GSH biosynthesis pathway. These measurements coincide with previous reports demonstrating a higher amount of GSH in roots of Medicago truncatula (Innocenti et al, 2007) and maize leaves (Mello et al, 2012) after GSNO and SNP treatment, respectively. In both cases, an enhanced expression of the γ-glutamylcysteine synthetase and GSH synthetase gene was detectable suggesting a NO-dependent transcriptional regulation of GSH production.…”
Section: Discussionsupporting
confidence: 92%
“…Although the mechanism of SeO 3 2− assimilation in roots remains unclear, some studies have demonstrated that GSH can greatly facilitate SeO 3 2− uptake by non‐enzymatically reduction of SeO 3 2− to SeCys in plant roots ( Xu et al, ; Mello et al, ). Hence, we focused on the effect of NO on GSH biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular analysis suggests that NO is a potential regulator of gene expression (Besson-Bard et al, 2009). Numerous putative NO-responsive genes related to stress, plant defense and hormonal responses have been identified (Polverari et al, 2003;Parani et al, 2004;Moreau et al, 2010;Mello et al, 2012). In addition, Innocenti et al (2007) reported that the NO donor sodium nitroprusside (SNP) mediated GSH synthesis by up-regulating the gene expression of two enzymes of GSH synthesis, including γ-glutamylcysteine synthetase (γ-ECS) and glutathione synthetase (GS) in Medicago truncatula roots.…”
Section: Introductionmentioning
confidence: 99%